OCCUPATIONAL CONTACT DERMATITIS - Saravanan Krishnan; I Gusti Ketut Darmada; Luh Made Mas Rusyati (Bali Journal of Medical and Health Sciences, 2013)
Occupational contact dermatitis is one of the most common work-related illnesses in many developed countries, accounting for up to one third of all occupational diseases. A high prevalence has been documented in specific occupational groups, such as construction workers, nurses, hairdressers, food processing workers and metal workers. Irritant contact dermatitis and allergic contact dermatitis are known as the two type of occupational contact dermatitis. Reddening of skin, blister, itchiness are symptoms of these dermatitis. Knowledge of the factors which predispose to occupational contact dermatitis is useful in occupational health practice for the application of preventive measures and for career guidance for workers in high risk occupations. Thus to maintain an effective work flow and good health status of the workers both the company and the workers should consider manipulating the risk factors and try to decrease or prevent the occupational contact dermatitis from getting worst.